Opinion of medical students on the role of a physiotherapist in providing health services - Justyna Szpyt; Kacper Pajor; Adrian Wiatrak; Aleksandra Szylińska; Iwona Rotter (Kazimierz Wielki University, 2019)
Introduction. An extremely important aspect of the efficient work of the therapeutic team is the knowledge of the rights and the range of tasks of each specialist who is part of it. In order to increase the efficiency of the physiotherapist's activity in the treatment and rehabilitation of patients, on September 25, 2015, the Act on the Physiotherapist's profession was passed. Despite the fact that the Act is more than 3 years old, there are no reports on the awareness and opinions of medical circles about it. Objective of the study. The aim of the study was to examine the opinions of future doctors - students of the 4th, 5th and 6th year of the medical faculty on the role of a physiotherapist in providing health services. Material and methods. 225 people from several medical schools in Poland (144 women and 81 men) took part in the survey. The questionnaire was based on the Physiotherapist Act and included questions about the students' opinions on the physiotherapists' rights, their role and competence in the rehabilitation process. Results. A significant proportion of future doctors do not have full knowledge of some of the physiotherapist's rights and the range of tasks. As many as 48.8% of the respondents disagree or have no opinion on the physiotherapist's possibility to refuse to perform the services ordered by a physician. Almost every third person thinks that physiotherapists do not have enough knowledge to conduct the functional diagnosis of the patient. According to 29.3% of respondents, a physiotherapist can not expect a physician to justify an order for physiotherapy. On the other hand, the vast majority of the study group believes that the physiotherapist should look after the patient from the first day after the surgery and consider the physiotherapist an inseparable part of the therapeutic team. As many as 84% of students want to cooperate with a physiotherapist in the future. Conclusions. 1. A significant percentage of students of medicine estimate the competences and skills of physiotherapists to be lower than guaranteed by the Act on the Profession of Physiotherapy. 2. The awareness of students of medicine regarding the competences of physiotherapists set out by the Act is insufficient, which may decrease the efficiency of a healthcare team. 3. Students of medicine consider the role of physiotherapists in the process of treatment and recovery of patients significant.